Revisiting the Interest Rate Effects of Federal Debt - Plante, Michael D.; Richter, Alexander W.; Zubairy, Sarah (The Review of Economics and Statistics, 2026)
Abstract This paper revisits the relationship between federal debt and interest rates in the U.S. A common approach is to regress long-term forward interest rates on long-term projections of federal debt. We show that issues regarding nonstationarity have become more pronounced over the last 20 years, significantly biasing recent estimates. Estimating the model in first differences rather than in levels addresses these concerns. We find that a 1 percentage point increase in the debt-to-GDP ratio raises the 5-year-ahead, 5-year Treasury rate by about 3 basis points. Roughly half of the interest rate response is driven by a higher nominal term premium.